Efeito de enxaguatórios bucais clareadores pré-escovação no desgaste abrasivo do esmalte dental - Bonicio, Gabrielle Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The aim of this study was to evaluate the effect of whitening mouthwashes used before toothbrushing on abrasive wear on enamel. Eighty bovine enamel specimens were obtained. Initial Knoop microhardness and profile of each surface specimens were measured. The specimens were randomly distributed among 4 groups (n=20): PW: Plax Whitening; LW: Listerine Whitening Before Brushing; U: Ultradex; C: Control. The specimens were immersed in mouthwashes for 1 min and brushed in a toothbrushing machine with 10 strokes, using a slurry composed of diluted dentifrice in artificial saliva (3:1). The specimens were washed with ultrapure water and immersed in artificial saliva for 30 min. A total of 540 cycles were performed. Final microhardness and surface roughness were reassessed and the surface loss in micrometers was measured. The specimens were immersed in saliva for additional 30 days and microhardness was performed. One-way ANOVA and Tukey tests were performed to analyze data (5%). Significant differences were observed for microhardness after treatment (p= 0.000045) and enamel loss (p=0.00001). For Tukey test: Microhardness: U (320.08±13.86)a, PW (323.58±32.75)a, LW (331.66±24.74)a, C (354.24±16.40)b. Wear (μm): PW (10.03±0.94)a, LW (9.92±0.81)a, U (8.88±1.02)b, C (6.56±0.91)c. After the immersion in saliva for 30 days, no significant statistics differences among the groups for microhardness were found. In conclusion, the use of mouthwashes reduced the enamel microhardness and increased enamel loss in comparison with control group; and the chlorine dioxide-based mouthwashes promoted the highest enamel loss compared to the peroxide-based ones

O objetivo deste estudo foi avaliar o efeito dos enxaguatórios bucais clareadores pré-escovação no desgaste abrasivo do esmalte dental. Foram preparados 80 espécimes de esmalte dental bovino. A microdureza e os perfis iniciais foram mensurados. Os espécimes foram distribuídos em 4 grupos (n = 20): PW: Plax Whitening; LW: Listerine Whitening pré-escovação; U: Ultradex; C: Controle. Os espécimes foram imersos nos enxaguatórios por 1 min e escovados por uma máquina de escovação com 10 golpes, utilizando uma mistura de dentifrício e saliva artificial (3:1). Os espécimes foram lavados em água ultra pura e imersos por 30 min em saliva artificial. No total foram realizados 540 ciclos. A microdureza e o perfil final dos espécimes foram reavaliadas e a perda de esmalte dental em micrometros foi mensurada. Os espécimes foram imersos em saliva artificial por mais 30 dias e a microdureza foi mensurada. Os dados foram analisados com o teste ANOVA um fator e Tukey (5%). Diferenças estatisticamente significantes foram observadas para a microdureza após os tratamentos (p= 0,000045) e para a perda de esmalte dental (p= 0,00001). Para o teste de Tukey: Microdureza: U (320.08±13.86)a, PW (323.58±32.75)a, LW (331.66±24.74)a, C (354.24±16.40)b. Desgaste: PW (10.03±0.94)a, LW (9.92±0.81)a, U (8.88±1.02)b, C (6.56±0.91)c. Após a imersão em saliva por 30 dias, nenhuma diferença estatística significante entre os grupos foi encontrada. Concluiu-se que, o uso dos enxaguatórios reduziu a microdureza do esmalte com aumento do desgaste em comparação ao grupo controle; e os enxaguatórios à base de dióxido de cloro promoveram uma maior perda de esmalte comparado àqueles a base de peróxidos
Keywords: Antissépticos bucais; Esmalte dentário; Clareadores dentários; Abrasão dentária